Pendampingan dalam penentuan besaran biaya produksi untuk usaha keripik dengan menggunakan metode Activity Based Costing - Dewi Sukmasari; Yenni Agustina; Agrianti Agrianti; Susi Sarumpaet (Penerbit Goodwood, 2020)
Purpose: The cost of production is an important component in determining the selling price. The right and accurate cost of goods manufactured can provide the right information for decision-makers. Kelurahan Tanjung Raya is one of the sub-districts located in the subdistrict of peace. One form of a business carried out by the home industry is the chips business. The chip business is one of the businesses that can help the family economy. This PkM partner is the Dasawisama Women chip business group in the Tanjung Raya sub-district, RT 015. The main problem of partners is that they are still biased in calculating the cost of goods manufactured, while the production cost is an essential component in determining the selling price. The PkM method provided is in the form of training and mentoring. As the results of this activity, the respondent welcomed this activity with a positive response and increased understanding of the respondents in comparing the cost of goods manufactured with the conventional method and the ABC method. The purpose of this study was to increase the skill and the knowledge of participants. Method: The activities carried out were training and accompaniment. Results: Respondents welcomed this activity with a positive response and increased respondent understanding in comparing the cost of goods manufactured comparisons with the conventional method and the ABC method. Conclusion: This activity has a positive impact on increasing the skills and income of the participant group. Keywords: Cost of production, ABC, Selling price